2019
DOI: 10.5114/biolsport.2019.85453
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent female soccer players’ soccer-specific warm-up effects on performance and inter-limb asymmetries

Abstract: No studies have assessed whether changes in physical performance and inter-limb asymmetries (ILA) can be achieved with the FIFA 11+ prevention programme in adolescent female soccer players. The aim of this study was to assess the effect of the FIFA 11+ programme compared with a standard warm-up on physical performance and ILA in adolescent female soccer players. Thirty-six adolescent female soccer players were randomly assigned to an experimental (EG; n = 19) or a control group (CG; n = 17). Unilateral/bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
81
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 38 publications
7
81
3
1
Order By: Relevance
“…Our findings and others 34,41 have observed significant improvements in change of direction ability in adolescent female soccer players. It has been described that to achieve the fastest performance during a change of direction test; larger contributions of isometric and eccentric strength, higher braking and propulsive forces and lower contact times, are all required 42 Despite the apparent critical relevance of between-limb imbalance for protection against injury and performance 17,18 , to the best of our knowledge, this is one of the first study to assess the impact of a training intervention on lower-extremity asymmetries in adolescent female soccer players 4 . Nevertheless, the current CSPT program did not make any meaningful changes in inter-limb asymmetries.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our findings and others 34,41 have observed significant improvements in change of direction ability in adolescent female soccer players. It has been described that to achieve the fastest performance during a change of direction test; larger contributions of isometric and eccentric strength, higher braking and propulsive forces and lower contact times, are all required 42 Despite the apparent critical relevance of between-limb imbalance for protection against injury and performance 17,18 , to the best of our knowledge, this is one of the first study to assess the impact of a training intervention on lower-extremity asymmetries in adolescent female soccer players 4 . Nevertheless, the current CSPT program did not make any meaningful changes in inter-limb asymmetries.…”
Section: Resultsmentioning
confidence: 95%
“…Nevertheless, the current CSPT program did not make any meaningful changes in inter-limb asymmetries. Pardos-Mainer et al 4 reported that a neuromuscular training program was effective at reducing the drop jump (ES: 0.72) and change of direction (ES: 0.93) asymmetries. When viewing the asymmetry results in Table 4, it is evident that the SD is quite large relative to the mean value; more so than for other test metrics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected studies were submitted to the PEDro methodological quality scale. Two studies obtained a score of 9/10 [ 36 , 37 ], one study obtained 8/10 [ 38 ], six obtained 7/10 [ 5 , 6 , 39 , 40 , 41 ], two obtained 5/10 [ 42 , 43 ], and two obtained 4/10 [ 44 , 45 ]. Table 1 displays the complete and detailed PEDro scale score of each study.…”
Section: Resultsmentioning
confidence: 99%
“…Different intervention programs, such as neuromuscular training, plyometric training (PT), strength training (ST) or power training [ 5 , 6 , 7 , 8 ], have been performed to improve physical capacities. However, there are discrepancies about which are the best exercises to improve female soccer players’ performance due to the lack of studies.…”
Section: Introductionmentioning
confidence: 99%